2010
DOI: 10.1111/j.1468-2257.2010.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

A Micro‐Simulation Approach to Modelling Spatial Unemployment Disparities

Abstract: This paper aims to construct a comprehensive model capable of simulating spatial unemployment disparities. The key feature of the model is that it simultaneously deals with commuting and migration. Much of the existing literature simply models one adjustment mechanism at a time. This paper adopts a micro-simulation approach to build a model which can deal with equilibrium and disequilibrium unemployment disparities in a context where commuting and migration are possible. The model is then used to demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…The conducted analyses confirm that geographic location proves to be the substantial differentiating factor for rural boroughs. We found that such rural boroughs perform better than peripheral rural boroughs from the demographic, business and infrastructure perspective, which confirms the deconcentration hypothesis for Poland, similarly to the studies for other countries presented in [Renkow, Hoover 2000;McArthur et al 2010;Partridge et al 2010;Marek et al 2017]. The deconcentration hypothesis works for Poland for a 40 km distance between the centres of the two administration entities, which translates into a 20-60 km distance to the provincial capital for the RB's inhabitants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The conducted analyses confirm that geographic location proves to be the substantial differentiating factor for rural boroughs. We found that such rural boroughs perform better than peripheral rural boroughs from the demographic, business and infrastructure perspective, which confirms the deconcentration hypothesis for Poland, similarly to the studies for other countries presented in [Renkow, Hoover 2000;McArthur et al 2010;Partridge et al 2010;Marek et al 2017]. The deconcentration hypothesis works for Poland for a 40 km distance between the centres of the two administration entities, which translates into a 20-60 km distance to the provincial capital for the RB's inhabitants.…”
Section: Discussionsupporting
confidence: 87%
“…For Canada, the commuting distance, which supports the deconcentration hypothesis, amounts to up to 120 km (but with the mean distance of 61 km). Similarly, [McArthur et al 2010] model the spatial unemployment disparities in Norway. The study shows that they grow sharply when the distance between two regions exceeds 80 km.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller towns, with a population of approximately 100,000 people, do not exert such an influence on RBs. The conducted analyses confirm that the entities located close to large towns perform better than peripheral RBs from the demographic, business and infrastructure perspective, which confirms the deconcentration hypothesis for Poland, similarly to the studies for other countries by Renkow and Hoover (2000), McArthur et al (2010), Partridge et al (2010) and Marek et al (2017). The deconcentration hypothesis works for Poland for a 40 km distance between the centres of the two administration entities, which translates into 30-50 km distance to the PC for the RB's inhabitants.…”
Section: Discussionsupporting
confidence: 78%
“…First, one problem with the current literature is that commuting is often neglected as a mechanism to cancel rural unemployment gaps. This is despite the presence of previous literature that concludes that commuting dominates the adjustment process (by filling gaps in local unemployment) (see, e.g., Renkow et al, ; Renkow, ; Partridge et al, ; McArthur et al, ). This paper adds to that literature by examining whether commuting is a way to backfill losses of local jobs.…”
Section: Introductionmentioning
confidence: 81%